POSTER DAN LEAFLET SEBAGAI MEDIA UNTUK PENINGKATAN PENGETAHUAN TENTANG HIPERTENSI PADA USIA LANJUT DI PADUKUHAN KALIRANDU RT 25 BANGUNJIWO, KASIHAN, BANTUL - Yuniar Wardani; Sari Ayu Maharani Putri (Universitas Pahlawan Tuanku Tambusai, 2022)
High blood pressure is an increase in blood pressure above the standard value where the systolic pressure is 140 mmHg, or the diastolic blood pressure is 90 mmHg. Community service activities aim to conduct assessments and provide preventive and promotive actions in patients with hypertension. The activity was carried out in the Kalirandu Hamlet RT 05, Bangunjiwo, Kasihan, Bantul. The method used is descriptive quantitative analysis, and the sample size is 31 elderly. Hypertension is a priority problem that arises based on the ultrasound approach. Increasing knowledge, awareness, and adherence to taking hypertension drugs is done by providing educational media in the form of posters and leaflets. Keywords:Hypertension, Elderly, Posters and Leaflets